REKONSTRUKSI PERTANGGUNGJAWABAN PIDANA TERHADAP TINDAK PIDANA KORUPSI APBD YANG DILAKUKAN OLEH ANGGOTA DPRD - Noor Aziz Said (Jurnal Dinamika Hukum, 2011)
Indonesia's national legal system based on modern law with a philosophy liberalism, individualism and rationalisme background of the nineteenth century in Europe (Penal Code), that contains the class characteristics. The characteristics of the national law classes imply of the Court as a judicial dictatorship. The existence of three different decision in terms of budget corruption committed by members of parliament, namely decision-free, loose and criminal verdict in the same case is proof of the dictatorship of the Court. To prevent the necessary expansion of the meaning of a judicial dictatorship legality principle, from the formal justice-procedural justice toward substantial material with 3-integral approach, the approach of juridical science religious, juridical contextual, and insightful approach to comparative/global recall the problem of corruption is an issue international. In addition it needs to be revisited Constitutional Court Decision No. 003/PUU-IV/2006 to be replaced with understanding the material unlawfully receiving AVAW as set forth in Supreme Court Jurisprudence No. 42 K/Kr/1965 and also article 2 and article 5 of Law. 48 of 2009 and the possible penal settlement by mediation. Keywords   : modern law, judicial dictatorship, reconstruction of criminal responsibility, criminal acts of corruption.